Message from the Executive Director - Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2012)
The ORNAC Board of Directors has been actively addressing the future of ORNAC through strategic planning, the Board Governance Initiative, and the development of the ORNAC Pillars (through which the work of the Board will be implemented in future). The Chairs of the five ORNAC Pillars have, during the past few months, been appointed by the ORNAC Board. They are Margot Walsh, St. John’s, NL, for National Conference Planning; Tracie Scott, of Markham, ON, for Professional Practice; Pat Pocock of Lucan, ON (By-laws and Nominations) and Bonnie McLeod of Maple Ridge, BC (Collaborative Initiatives) will Co-Chair the Advocacy pillar; Christina Bilopavlovic of Hamilton, ON, for Research and Informatics; and Charlotte Roach of Aroostook, NB, for Marketing. ORNAC is in the process of completing the Terms of Reference, for each Pillar, for review/approval by the Board.